On limit cycles in regularized Filippov systems bifurcating from homoclinic-like connections to regular-tangential singularities - Novaes, Douglas D.; Rondón, Gabriel [UNESP] (Elsevier, 2022)
In this paper, we are concerned about smoothing of Filippov systems around homoclinic-like connections to regular-tangential singularities. We provide conditions to guarantee the existence of limit cycles bifurcating from such connections. Additional conditions are also provided to ensure the stability and uniqueness of such limit cycles. All the proofs are based on the construction of the first return map of the regularized Filippov system around homoclinic-like connections. Such a map is obtained by using a recent characterization of the local behavior of the regularized Filippov system around regular-tangential singularities. Fixed point theorems and Poincaré–Bendixson arguments are also employed.
Keywords: Limit cycles; Nonsmooth differential systems; Regularization; Tangential singularities; Σ–polycycles